Simultaneous determination of thiamethoxam and its metabolite clothianidin by LC-MS/MS in goji berry and soil. Issue 8 (21st June 2019) - Li, Wei; Shen, Shuo; Chen, Hongyu; Guo, Qingyun
ABSTRACT: In this study, an effective analytical method for simultaneous determination of thiamethoxam and its metabolite clothianidin in goji berry and soil was developed by liquid chromatography-tandem mass spectrometry (LC-MS/MS). The recoveries of the compounds in goji berry and soil at the levels of 0.005, 0.02, and 0.1 μg kg −1 were 84.7–98.9% and the relative standard deviations (RSDs) were 0.9–3.2%. The limits of detection (LOD) for both compounds in goji berry and soil matrices were 0.001 mg kg −1 ; the limits of quantification (LOQ) were 0.005 mg kg −1 for both compounds in two matrices. The dissipation and final residual experiments in 2016 with the commercial formulation of dinotefuran thiamethoxam 30% suspension concentrate (SC) was conducted in goji berries in northwest China (Qinghai, Gansu, Inner Mongolia, and Ningxia). Thiamethoxam was dissipated fast in goji plant ecosystem with half-lives were 1.08–1.01 and 2.04–4.25 days in goji berry and soil. The final residues of thiamethoxam were <0.005–0.382 and <0.005–1.120 mg kg −1 in goji berry and soil, respectively.